THE ACOUSTICS EMISSION SYSTEM OF THE CRACKS PLACE LOCATION - Lutskiy, Maksym G.; Ponomarenko, Aleksandr V. (Proceedings of National Aviation University (archive), 2010)
The structure of the construction of the acoustics emission system of the place location of through defects is considered in product lines. It is shown that the use of technology of LabCard allows to conduct the redistribution of functions between electronic and programmatic facilities of the system. The structure of electronic program facilities are considered. The forming principles of the multilevel control system are shown, that allows to conduct modification of the system without the change of its electronic facilities. The examples of work of programmatic facilities of the system are resulted.